Assessment of the Quality and Credibility of Literature in Academic Research - Elyas, Titip; Sagita, Widya; Fitriani, Wahidah (Universitas Pahlawan Tuanku Tambusai, 2025)
Literature has a fundamental role in the academic world, especially at the master's and doctoral levels, as the foundation for scientific development. However, in the digital era marked by a flood of information, the assessment of the quality and credibility of literature has become increasingly complex. Researchers and students are not only required to find relevant sources, but also trustworthy and high-quality sources. This challenge is exacerbated by the rise of predatory journals, scientific disinformation, publication pressure, and an over-reliance on metrics such as the Impact Factor, which has the potential to obscure the scientific quality of a work. This article aims to explain and dissect the criteria and techniques in assessing the quality and credibility of scientific literature. In addition, this study also aims to compare the characteristics of academic sources with popular literature to help researchers choose the right and scientifically responsible sources. This study uses a literature study approach with descriptive analysis of various academic literature sources that discuss the assessment of the quality of scientific publications. Data were obtained from books, reputable journal articles, and relevant academic guidelines, then analyzed to identify criteria and techniques for evaluating the literature. The results of the discussion show that the assessment of the quality of literature needs to be carried out comprehensively by considering the credibility of the author, the reputation of the publisher, the peer review process, the relevance of the content, and the methodological context. The practical implication of this research is the availability of conceptual and technical guidance for researchers and students in facing literary challenges in the digital era, so as to maintain research integrity and improve the quality of scientific work.